1990
DOI: 10.1111/j.1600-051x.1990.tb01064.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of overhanging dental restorations and their relationship to periodontal disease

Abstract: Overhanging dental restorations (ODR) are a major dental health problem. An ODR is defined as an extension of restorative material beyond the confines of a cavity preparation. They have been strongly implicated as an etiologic factor in the progression of periodontal disease and are alarmingly prevalent. In addition to promoting plaque accumulation, they change a nondestructive subgingival flora to a destructive one. There is good documentation that bleeding, gingivitis, and bone loss increase in tissues adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 24 publications
1
11
0
4
Order By: Relevance
“…Data on such details are not recorded in the Dunedin Study. However, previous studies suggest that a large proportion of approximal dental restorations (between 20% and 76%) have overhanging or poorly contoured margins, although estimates vary widely depending on both the methods for determining overhangs and the population studied (Brunsvold & Lane 1990, McDonald & Pack 1990, Albandar et al 1995. Other studies have suggested that different dental materials may pose differential risks for periodontal CAL (Paolantonio et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Data on such details are not recorded in the Dunedin Study. However, previous studies suggest that a large proportion of approximal dental restorations (between 20% and 76%) have overhanging or poorly contoured margins, although estimates vary widely depending on both the methods for determining overhangs and the population studied (Brunsvold & Lane 1990, McDonald & Pack 1990, Albandar et al 1995. Other studies have suggested that different dental materials may pose differential risks for periodontal CAL (Paolantonio et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Brunsvold, Lane 4 (1990) and Reitemeier et al 12 (2002) found higher loss of attachment in places adjacent to maladapted restorations. Other studies 8 showed higher values of CAL in subgingivally located restorations, independently of the observed adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies, however, focus on different aspects of the relationship between dental materials, surface characteristics, adaptation, etc., thus providing guidelines for the dental team. 2,4,12 Previous studies looking at this subject have suggested that crowns may frequently be a problem to the periodontium. 15 At the moment these studies were performed, however, some confusion between gingival inflammation and periodontal breakdown existed, ultimately leading to misleading conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La longitud de la corona clínica es importante en la planificación de la restauración de un diente 7 y en este aspecto, la preservación del ancho biológico periodontal juega un rol relevante en la biología de los tejidos periodontales 8 , ya que el daño al periodonto es elevado cuando se realiza un procedimiento restaurador con márgenes subgingivales 9 . Las restauraciones que invaden el ancho biológico periodontal promueven la acumulación de placa bacteriana, cambios negativos en la flora subgingival, sangrado en el sondaje 10 , disminución significativa en bacterias grampositivas y aerobias, con un aumento significativo en la microbiota gramnegativa anaeróbica 11 y, finalmente, pérdida de inserción periodontal 12 .…”
Section: Introductionunclassified